Neutrophil extracellular traps: Their role in periodontal disease - Kolaparthy, Lakshmi Kanth (J Indian Soc Periodontol, 2014)
Neutrophils are the first line of innate immune defense against infectious diseases. Since their discovery, they have always been considered tissue-destructive cells responsible for inflammatory tissue damage occurring during infections. Extensive research in the field of neutrophil cell biology and their role skewing the immune response in various infections or inflammatory disorders revealed their importance in the regulation of immune response. Neutrophils also release neutrophil extracellular traps (NETs) for the containment of infection and inflammation along with other antimicrobial molecules. Activated neutrophils provide signals for the activation and maturation of macrophages as well as dendritic cells. Neutrophils are also involved in the regulation of T-cell immune response against various pathogens and tumor antigens. Thus, the present review is intended to highlight the emerging role of neutrophil extracellular trap production in the regulation of immune response and its role in periodontal disease.